PENGARUH PERENCANAAN DESTINASI DAN PARTISIPASI MASYARAKAT TERHADAP KEBERLANJUTAN PARIWISATA DI TANJUNG KASUARI KOTA SORONG - Murni; Rasma Widya Handyni (Accounting Student Series on Emerging Trends, 2026)
This study aims to analyze the influence of destination planning and community participation on tourism sustainability at Tanjung Kasuari, Sorong City. A quantitative approach using the SEM-PLS method was applied to 120 respondents selected through purposive sampling. Results indicate that: (1) destination planning has a significant positive effect on tourism sustainability (β = 0.381; T = 4.201; p = 0.000; f² = 0.158); (2) community participation has a significant positive effect on tourism sustainability (β = 0.399; T = 4.912; p = 0.000; f² = 0.173). The model explains 51.3% of tourism sustainability variance (R² = 0.513) with GoF = 0.616 (strong fit) and Q² = 0.498 (strong predictive relevance). These findings underscore the importance of synergizing comprehensive destination planning and active community participation to achieve sustainable tourism in Papua Barat Daya coastal areas.